Simulation of the Vibration Characteristics for Agricultural Wheeled Tractor with Implement and Front Axle Hydropneumatic Suspension - Enlai Zheng; Song Cui; Yuanzhao Yang; Jinlin Xue; Yue Zhu; Xiangze Lin (Shock and Vibration)
The dynamic model is significant for the analysis of the vibrational characteristics of the wheeled tractor system with implement and front axle hydropneumatic suspension. In this work, the nonlinear stiffness and damping equations are derived first. The dynamic coupling relationship among cabin, three-point hitch structure, and implement are figured out, and the dynamic model of the half agricultural wheeled tractor/implement system is presented considering the effects of three-point hitch structure, passive silent blocks of cabin, and front axle hydropneumatic suspension together. To validate the model, the power spectral densities (PSDs) of the driver seat, cabin, chassis, and implement acquired from numerical simulations are compared with those from experiments, respectively. Under different forward speeds, two groups of results match well. Based on the model, the influences of passive cabin suspension, implement, and front axle hydropneumatic suspension on the dynamical characteristics of the tractor system are investigated. Results indicate that the front axle hydropneumatic suspension will deteriorate the ride comfort of the driver but improve the handing stability. The passive cabin suspension reduces the operational stability while improving much more ride comfort than the front axle hydropneumatic suspension does. The driver’s comfortableness will be increased due to implement; meanwhile, handling stability will be compromised. Besides, the impacts of initial nitrogen volume, pressure of accumulators, and orifice diameter of throttle valves on the vibration characteristics of the tractor system are also inspected.